Strategi Kepala Sekolah Dalam Peningkatan Kinerja Guru Di SMK Muhammadiyah 7 Gondanglegi - Kusnul Kotimah; Abdulkadir Rahardjanto (Jurnal Kebijakan dan Pengembangan Pendidikan, 2017)
Abstract: This research aims to know the principal's strategy in improving teacher performance. The focus of this study was to find out how the strategy was carried out by the School Principal in Improving Teacher Performance in Gondanglegi 7 SMK Muhammadiyah. This research was conducted with a descriptive qualitative approach. The subjects of the study were the school principal, deputy headmaster and 2 teachers at SMK Muhammadiyah 7 Gondanglegi. Data collection techniques through observation, interviews, and documentation. Data analysis in this study was based on Miles and Huberman's steps: data collection, data presentation, data reduction, and conclusion drawing/verification. The results of the study show how the strategies are undertaken by the principal in improving teacher performance in SMK Muhammadiyah 7 Gondanglegi, starting from the planning made by the school principal, the implementation carried out by the principal; Discipline, Motivator, and Rewards and Punishment, the evaluation conducted by the principal consists of Attendance, MSG, sustainable professional development (PKB), Administration, School activities to improve teacher performance and student questionnaires.Keywords: Strategy, Principal, Teacher Performance Abstrak: Penelitian ini bertujuan untuk mengetahui stategi kepala sekolah dalam peningkatan kinerja guru. Penelitian ini dilakukan dengan pendekatan kualitatif deskriptif. Subjek penelitian adalah kepala sekolah, wakil kepala sekolah dan 2 guru yang ada di SMK Muhammadiyah 7 Gondanglegi. Teknik pengumpulan data melelui kegiatan observasi, wawancara dan dokumentasi. Analisis data dalam penelitian ini didasarkan atas langkah-langkah Miles dan Huberman: pengumpulan data, penyajian data, reduksi data dan penarikan kesimpulan / verifikasi. Hasil penelitian menunjukan bagimana strategi yang dilakukan kepala sekolah dalam peningkatan kinerja guru di SMK Muhammadiyah 7 Gondanglegi, mulai dari perencanaan yang dilakukan kepala sekolah, pelaksanaan yang dilakukan kepala sekolah; Kedisiplinan, Motivator dan Rewads dan Punishment, evalusi yang dilakukan kepala sekolah terdiri dari: Kehadiran, MSG, pengembangan keprofesionalan berkelanjutan (PKB), Administrasi, Kegiatan sekolah guna meningkatkan kinerja guru dan angket siswa.Kata kunci: Strategi, Kepala Sekolah, Kinerja Guru